2013
DOI: 10.2134/jeq2012.0273
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potential Impacts of a Wastewater Rapid Infiltration Basin System on Groundwater Quality: A Delaware Case Study

Abstract: Rapid infiltration basin systems (RIBS) are receiving increased interest for domestic wastewater disposal in rural areas. They rely on natural treatment processes to filter pollutants and use extremely high effluent loading rates, much greater than natural precipitation, applied to a small geographic area instead of disposal to surface water. Concerns exist today that adopting RIBS in areas with shallow groundwater and sandy soils may increase ground and surface water pollution. We conducted a field study of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
(49 reference statements)
2
11
0
Order By: Relevance
“…Likewise, our analysis of WSP as a function of SPSC was generally in keeping with recent work. In previous studies, negative SPSC values were associated with significant increases in soluble P release from soils (Andres & Sims, 2013;Chakraborty et al, 2012;Nair & Harris, 2014;Oladeji, O'Connor, Sartain, & Nair, 2007). Similarly, in our study, negative SPSC values were associated with a significant linear increase in WSP loss (R 2 = 0.52) (Figure 2a).…”
Section: Phosphorus Release From Soilssupporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, our analysis of WSP as a function of SPSC was generally in keeping with recent work. In previous studies, negative SPSC values were associated with significant increases in soluble P release from soils (Andres & Sims, 2013;Chakraborty et al, 2012;Nair & Harris, 2014;Oladeji, O'Connor, Sartain, & Nair, 2007). Similarly, in our study, negative SPSC values were associated with a significant linear increase in WSP loss (R 2 = 0.52) (Figure 2a).…”
Section: Phosphorus Release From Soilssupporting
confidence: 86%
“…Similarly, in our study, negative SPSC values were associated with a significant linear increase in WSP loss (R 2 = 0.52) (Figure 2a). Sites with no recent history of P management (i.e., TPAC [ Table 2]) had positive SPSC values with minimum P release to soil solution, a result consistently observed in prior work (Andres & Sims, 2013;Nair & Harris, 2004, 2014Oladeji et al, 2007). Due to the rapid rate of change between negative SPSC and WSP compared with positive SPSC, zero SPSC has been suggested as an environmental threshold (Nair & Harris, 2004); our results support using a SPSC threshold value close or equal to zero, as no significant linear relationship existed between WSP values <0.01 and SPSC.…”
Section: Phosphorus Release From Soilssupporting
confidence: 77%
“…A recent literature review of threshold PSR values by researchers in different parts of the world (Nair, 2014) indicated that most soils tend to have a threshold PSR in the 0.10 to 0.15 range. Using a threshold PSR of 0.15, Andres and Sims (2013) showed that the PSR–SPSC concept was effective in risk assessment of P loss from a groundwater field monitoring site in Delaware, USA. Based on a visual observation of the threshold PSR of 0.04, Bhadha et al (2010) noted that SPSC values of surface soils in both wetlands and uplands in their study were negative and EPC 0 values and pore water P concentrations were high, indicating that all the soils were P sources.…”
Section: Resultsmentioning
confidence: 99%
“…Others have documented an association between negative SPSC and elevated solution P both in the field (pore water [31]) and laboratory (column leachates [19]). …”
Section: Legacy Phosphorus and Water Table Managementmentioning
confidence: 99%